Pelaksanaan Discharge Planning Pada Pasien Postpartum: A Narrative Review - Henny Yulianita; Firman Sugiharto; Risma Dwi Nur Pratiwi; Syifa Fauziah Mutaqin; Alfi Kusuma Dewi; Devi Futri Intan Maria (Jurnal Keperawatan Muhammadiyah, 2022)
Objective:  to describe the implementation of discharge planning by nurses in the Maternity Room. Methods:  This literature review uses was a narrative review design. The databases used were EbscoHost, Sciencedirect, PubMed, and Google Scholar. The strategy for searching articles using the PCC framework with the keywords “nurse” OR “nursing” OR “health care professional” AND “discharge planning” OR “discharge process” OR “discharge management” AND “postpartum” OR “postnatal” OR “after birth ". Results:  The results showed that 10 articles were analyzed and most of the articles said that the implementation of discharge planning was still not optimal. This was caused by several factors, namely unavailable guidelines, incomplete SOPs, busy staff, high workload, and unskilled staff. Conclusion:  Overall, the implementation of discharge planning in the post partum area is still not done optimally. Nurses are expected to increase their role in providing discharge planning in the postpartum so that patients are able to carry out self-care independently at home.